The Arabic Subtitles And the Language Acquisition Of Non-Native Learners Of Arabic In The Saudi Universities/ Ø§Ù„ØªØ±Ø¬Ù…Ø© Ø§Ù„Ù…Ø±Ø¦ÙŠØ© ÙˆØ£Ø«Ø±Ù‡Ø§ Ø¹Ù„Ù‰ Ø§ÙƒØªØ³Ø§Ø¨ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ù„Ù†Ø§Ø·Ù‚ÙŠÙ† Ø¨ØºÙŠØ±Ù‡Ø§ ÙÙŠ Ø§Ù„Ø¬Ø§Ù…Ø¹Ø§Øª Ø§Ù„Ø³Ø¹ÙˆØ¯ÙŠØ© - Omar, Abdulfattah; Altohami, Waheed (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Despite the increasing interest in investigating the influence of subtitles on the acquisition of second languages, including English, French, and Spanish, very little has been done in Arabic. This phenomenon may be attributed to the lack of the use of technological applications in teaching Arabic. So far, different universities have adopted traditional methods in teaching Arabic as a second language. In the face of this limitation, this study explores the impact of Netflix subtitles on improving the language acquisition of Arabic by non-native speakers of Arabic in Saudi universities. Both quantitative and qualitative methods were used for the analysis of the data set in question. The subject of the study, 68 participants from three Saudi universities: Imam Muhammad Ibn Saud Islamic University, Taibah University, and Prince Sattam Bin Abdulaziz University. The participants are in different disciplines, including Islamic Jurisprudence (Shariah), Arabic studies, engineering, and English. They also come from different countries, including Indonesia, Uzbekistan, Malaysia, and Bosnia and Herzegovina. Results indicate that subtitles can be usefully used to improve Arabic linguistic performance and acquisition by non-native speakers. Subtitles were helpful for the learners of Arabic in both the acquisition of standard and colloquial forms of the language. Saudi universities and other educational institutions are thus recommended to integrate subtitling and language technologies in teaching Arabic as a second language.